Media Richness, Social Influences and Electronic Mail in the Workplace - Bidin, Rosmiza (2000)
Social constructivist perspectives propose that communication technology is not objective, rather, it is a joint product of technological features and social interaction. Based on the above-mentioned perspectives, this study was designed to answer several research questions. The questions were (1) do people from the eastern culture perceive e-mail richness rating the same as the western people do; (2) is it true that co-workers, supervisors and medium expertise factors do contribute in the e-mail use and usefulness assessments of their peers; and (3) to what extent those factors influence individual's use and assessments of e-mail. The general objective of this study is to yield an empirical assessments of co-workers' and supervisors' influence on media assessments and use behaviour. The hypotheses presented were drawn based on the shared premises of three major streams of structuration perspectives, namely Structuration, symbolic interaction extension to Media Richness Theory, and Social Influence. The population of the study consisted of academic and non-academic staffs in UPM. Five faculties and one institute were randomly selected, and the Computer Centre provided 353 names of individual e-mail users of these faculties and institute. Self-administered questionnaires were sent to the all 353 users, but only 218 were usable. This study used survey method to collect data. Self-administered questionnaires were personally sent and collected by enumerators. All data were gathered and coded using Statistical Package for Social Sciences (SPSS 7.5). The statistical analyses used include frequency, percentage, mean, standard deviation, Pearson's correlation and, single and multiple regression analysis. The results showed that (1) media richness perception showed significance difference between eastern and western culture, (2) keyboard skills was significant antecedent to e-mail richness perception, and (3) social influences from co-workers and supervisors contributed significantly towards e-mail use and usefulness assessments of their peers. As a conclusion, it is very important to consider both technological features and social interaction in planning, implementing and maintaining the use of communication technology in organization.